Evaluating management options that use climate forecasts: Modelling livestock production systems in the semi-arid zone of South Africa - Thornton, Philip K.; Fawcett, R.H.; Galvin, K.A.; Boone, Randall B.; Hudson, J.W.; Vogel, C.H. (Inter-Research Science Center, 2004)
Drought is a frequent occurrence in the Northwest Province of South Africa, and it appears to be strongly influenced by El Niño-Southern Oscillation events. The South African Weather Services produce long-term seasonal climate forecasts for 3 and 6 mo in advance that could allow crop and livestock farmers to plan anticipated wet or dry seasons. We describe a simple economic model linked to an ecosystem model, and we report on the results of simulation runs designed to estimate the economic value of climate forecasts in the study area. For the communal farmers of this region, forecasts may have little direct economic value in terms of modifying management decisions, but they may have value in terms of optimal management for asset accumulation. For commercial farmers, model results suggest that long-term average annual income could increase through utilizing forecasts associated with El Niño-Southern Oscillation events, but at the cost of increased year-to-year variability in farm income. More work is required to investigate other possible management responses to forecast information, identify more clearly the situations where climate forecasts are potentially of value, and implement mechanisms for the delivery and utilisation of this information by livestock keepers in the region.